1991
DOI: 10.1148/radiology.180.1.2052703
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spine hyperextension injuries: MR findings.

Abstract: Cervical hyperextension injuries are common and often show minimal radiographic abnormalities, even with severe or unstable lesions. Fourteen patients, nine with acceleration hyperextension "whiplash" injuries and five injured by direct frontal head trauma, underwent magnetic resonance (MR) imaging within 4 months of injury. Five of seven patients with anterior spinal column injuries showed characteristic separation of the disk from the vertebral end plate, lesions still evident as late as 9 months after injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(61 citation statements)
references
References 0 publications
2
55
0
4
Order By: Relevance
“…Our study is comparable with previous whiplash studies concerning age, gender, and type of car accidents [45]. The frequency of residual symptoms in our study is equivalent to that in reports [14,31]. We found no significant differences between the three subgroups depending on severity of symptoms at follow-up and temperament and character.…”
Section: Discussionsupporting
confidence: 90%
“…Our study is comparable with previous whiplash studies concerning age, gender, and type of car accidents [45]. The frequency of residual symptoms in our study is equivalent to that in reports [14,31]. We found no significant differences between the three subgroups depending on severity of symptoms at follow-up and temperament and character.…”
Section: Discussionsupporting
confidence: 90%
“…A magnetic resonance imaging study demonstrated injuries to both components in whiplash patients, and similar injuries have also been discovered at surgery and autopsy [4,8,16]. Whiplash simulations using cadavers and monkeys have also produced ALL tears and anterior disc detachments [22,46].…”
Section: Introductionmentioning
confidence: 76%
“…Also, after 1 year it was observed that considerable headache was more frequent in the group with traumatic findings (OR 2.8; 95 CI 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and this group had a higher median headache intensity (Table 6). These above mentioned associations were not significant and the group did not differ otherwise from other participants ( Table 7).…”
Section: Associations Between Mri Findings and Outcomementioning
confidence: 99%
“…To explore the biological component of neck pain following whiplash injuries, studies of magnetic resonance imaging (MRI) have been performed in order to visualise potential damage to the cervical spine [3,4,8,17,[21][22][23]29]. Generally, very few identifications of traumatic lesions have been described in the acute phase after whiplash injuries and findings do not seem to be associated with the prognosis [4,17,29].…”
mentioning
confidence: 99%
See 1 more Smart Citation